Prospect Generation Studies of Cretaceous Sands, Khipro Area by Integrating Seismic and Well Data - Shakir, U.; Hussain, M.; Mahmood, M. F.; Amjad, M. R.; Zafar, W. A.; Mehmood, S.; Abideen, Z. U.; Tahir, A. R.; Haroon, M. (The Nucleus, 2020)
Khipro block is located in southern Indus Basin, Pakistan. Khipro area possesses good hydrocarbon potential, which is confirmed by several oil and gas discoveries in this area. This research paper is focused to delineate the subsurface structures favorable for hydrocarbon accumulation and remaining reservoir potential through integrated seismic structural analysis and petrophysical interpretation of Naimat Basal-01 and Siraj South-01 wells. Seismic structural interpretation confirms the normal faulting, in which elevated horst blocks are providing suitable trap for hydrocarbon accumulation. Mapping at Basal and Massive Sands level revealed that the existence of two compartments at reservoir level. The southwestern compartment is relatively shallower and has a great potential for future hydrocarbon explorations, as compared to northeastern compartment. Low shale volumes, good porosity values and high hydrocarbon saturation prove Massive Sands as a good reservoir in both wells.